Kemampuan Predasi Ikan Sepat (Trichogaster trichopterus) dalam Memangsa Larva Anopheles sp - Asmiani Asmiani; Sarjito Eko Windarso; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2013)
Malaria is still one of public health problems because it can lead to fatality, particularly among high risk groups, including infants, under five children and pregnant mothers. The utilization of larvae-eating fish for controlling mosquito larvae as biological method is highly recommended because it is safe and environmentally friendly. The objective of this study was to understand the predation capacity of sepat fish (Trichogaster trichopterus) on Anopheles sp larvae in the labo-ratory setting by conducting a true experiment of factorial with randomized groups design. There were six interventions as a result of the combination of three fish lengths (i.e. 4, 7 and 10 cm) and two water heights in aquarium (i.e. 10 and 100 cm). In each aquarium there were 10 larvaes and one healthy but three-day hungry fish, and for each intervention there was five replications. The number of larvae eaten by the fish was observed after 15 minutes. Result of the statistical test of one way anova multivariate test showed that predation capacities of sepat fish at various water levels and fish sizes were significantly different. Fish at 4 cm length in 10 cm water height had the highest predation capacity (mean: 9,2; SD: 1,09) compared with the other interventions. It is suggested that for further studies it is necessary to consider different research design as well as the other factors such as the size of larva instar, water type, and intervention time.